2012
DOI: 10.3349/ymj.2012.53.6.1099
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Eating Disorder Inventory-2: Psychometric Properties and Cross-Cultural Comparison

Abstract: PurposeThe purpose of the present study was to examine the validity and reliability of the Korean version of the Eating Disorder Inventory-2 (EDI-2) in Korean patients with eating disorders and healthy controls, and to investigate cultural differences of EDI-2 between a Korean group and a North American standardization sample.Materials and MethodsThe Korean version of the EDI-2 was prepared after comprehensive clinical assessment of Korean patients with eating disorders (n=327) as well as female undergraduates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another limitation is that majority of the AN group were binge-eating purging type (restrict type ¼6; binge-eating/purging ¼12) and had similar EDI scores compared to the BN group. Previous studies have reported that the EDI subscale scores are hard to differentiate AN binge-eating/purging type from BN (Garner 1991;Lee et al, 2012). Another thing to consider is that majority of our subjects (17 of 18 AN patients and all of the BN patients) were taking selective serotonin reuptake inhibitors (SSRIs).…”
Section: Discussionmentioning
confidence: 90%
“…Another limitation is that majority of the AN group were binge-eating purging type (restrict type ¼6; binge-eating/purging ¼12) and had similar EDI scores compared to the BN group. Previous studies have reported that the EDI subscale scores are hard to differentiate AN binge-eating/purging type from BN (Garner 1991;Lee et al, 2012). Another thing to consider is that majority of our subjects (17 of 18 AN patients and all of the BN patients) were taking selective serotonin reuptake inhibitors (SSRIs).…”
Section: Discussionmentioning
confidence: 90%
“…The EDI‐2 is a self‐report test with 11 subscales that measure symptoms and psychological factors associated with EDs: drive for thinness, bulimia, body dissatisfaction, ineffectiveness, perfectionism, interpersonal distrust, interoceptive awareness, maturity fears, asceticism, impulse regulation, and social insecurity (Garner, ). The Cronbach's alpha value for the EDI‐2 is .77–.93 for Koreans (Lee et al., ). The BDI is a self‐report questionnaire that evaluates the intensity of depression (Beck et al., ); the Cronbach's alpha value for the BDI is .85 for Koreans (Hwang et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…2 History of NSSI (positive/negative) and its frequency were evaluated after interviews with the psychiatrist. In addition, in order to objectively evaluate eating psychopathology and other psychopathological features, such as depressing, anxiety, and obsessive-compulsive behavior, we asked all of the subjects to complete self-report questionnaires, such as Eating Disorders Inventory-2 (EDI-2), 23 Beck Depression Inventory (BDI), 24 Beck Anxiety Inventory (BAI), 25 Maudsley Obsessive Compulsive Inventory (MOCI). 26 …”
Section: Methodsmentioning
confidence: 99%
“… 23 27 The Cronbach's alpha value for the EDI-2 is 0.77–0.93 for Koreans. 23 The MOCI is a 30-item self-report test that assesses four types of obsessive compulsive complaints: checking, washing, doubting, and slowness. The Cronbach's alpha value of MOCI is 0.80 for Koreans.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation